Mechanical property of C/SiC corrugated lattice core composite sandwich panels after high temperature annealing. (15th February 2019) - Yang, Fan; Wang, Xiao-hong; Zeng, Tao; Xu, Guo-dong; Cheng, Su; Chen, Hai-ming
Abstract: Carbon fiber reinforced silicon carbide (C/SiC) corrugated lattice core composite sandwich panels fabricated by precursor infiltration and pyrolysis (PIP) were treated at temperatures ranging from 1400 °C to 1800 °C. The effects of high temperature annealing on the physical and mechanical properties of the composite sandwich panels were investigated. With the annealing temperature increasing, the compression properties of the composite sandwich structures increased initially and then decreased reversely. Out of the three samples, the compression strength and the modulus of the specimen treated at 1400 °C are maximal at 3.50 MPa and 54.45 MPa, suggesting the optimal annealing temperature for mechanical properties is 1400 °C. Two competing mechanisms including crystallization and carbothermal reduction determined the mechanical properties of the composite sandwich structures. Furthermore, the high temperature mechanical properties of C/SiC corrugated lattice core composite sandwich panels after heat treatment were investigated.